Metaphorization Process of Gender Lexicon metaphorization Process Of Gender Lexicon (Journal of Pedagogical Inventions and Practices, 2024)
The article describes the process of metaphorization within the gender lexicon, aiming to uncover the underlying mechanisms through which gender-related concepts and identities are metaphorically constructed and understood. By analyzing linguistic data and cultural representations, the study seeks to elucidate how metaphorical language shapes perceptions of gender, influences social attitudes, and perpetuates gender norms and stereotypes. Through an interdisciplinary approach drawing on linguistics, cognitive science, and gender studies, the research contributes to a deeper understanding of the complex interplay between language, cognition, and social identity in relation to gender. This paper into the metaphorization process of the gender lexicon promises to shed light on the ways in which language reflects and reinforces societal beliefs about gender, ultimately informing efforts to promote gender equality and challenge traditional gender roles